Inflation dynamics in Brazil: an empirical approach - Oreng, Mauricio (2003)
This study examines the New Keynesian Phillips Curve (NKPC) in the context of the Brazilian economy, aiming to empirically test its validity. Based on Calvo's (1983) model, which incorporates price stickiness and rational expectations, the dissertation discusses criticisms of the traditional model, including the lack of inflation inertia and the negative relationship between the output gap and inflation acceleration. Using methodologies proposed by Gali and Gertler (1999), which replace the output gap with unit labor costs as a proxy, the research applies econometric tests to the Brazilian economy during the Real Plan period. The results are compared to those obtained for developed economies, contributing to the understanding of inflation dynamics in Brazil and its adherence to the NKPC framework.